Epistemologi Kitab Syarah Hadis “Manhāj Dhawī Al-Naẓar Fī Al-Sharḥ Alfiyyah ‘Ilm Al-Athar” Karya Syekh Maḥfūẓ Tarmas - Muhid, Muhid; Syabrowi, Syabrowi; Nurita, Andris (el Buhuth: Borneo Journal of Islamic Studies, 2023)
This article tries to examine the epistemology of the book of sharah hadith by Sheikh Mahfudz al-Tarmasi, “Manhāj Dhawi> al-Naz}ar fi> al-Sharh} Alfiyyah ‘Ilm al-Athar”. Sheikh Mahfudz al-Tarmasi himself is an Indonesian scholar from Pacitan who is very competent in the field of hadith. His books are scattered everywhere. However, this article will discuss one of his the book, “Manhāj Dhawi> al-Naz}ar fi> al-Sharh} Alfiyyah ‘Ilm al-Athar” from an epistemological aspect. Before entering into the core discussion, we first explain the notion of epistemology, biography, scientific rihlah and a number of works by Sheikh al-Tarmasi are also described. The research is in the form of library research. So the instrument used is documentation, namely utilizing data sources in the form of books, scriptures, and scientific papers that are relevant to this article. The data is then presented with a descriptive analysis method. The results of this study indicate that the book “Manhāj Dhawi> al-Naz}ar fi> al-Sharh} Alfiyyah ‘Ilm al-Athar” uses the tahlili method, namely the method used to explain the meaning of the hadith from its various aspects. The pattern used is a scientific style, because the style of discussion focuses on hadith science. While the data source is dominated by bi ra’yi sources. The work also meets the coherence theory criteria. So the validity of the book is no doubt.